Synergetic Effects of Combined Treatment of Colistin With Meropenem or Amikacin on Carbapenem-Resistant Klebsiella pneumoniae in vitro - Yu, Lan; Zhang, Jisheng; Fu, Yanjun; Zhao, Yongxin; Wang, Yong; Zhao, Jing; Guo, Yuhang; Li, Chunjiang; Zhang, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2019)
The resistance of carbapenem-resistant Klebsiella pneumoniae (CRKP) to colistin has become a major challenge in clinics. The objective of this study was to investigate the synergistic and bactericidal effects of combinations of colistin with meropenem and amikacin in vitro and provide laboratory data required for the treatment of CRKP infections in the Eastern Heilongjiang Province. The minimum inhibitory concentrations of antibiotics were determined by micro-broth dilution method against 40 CRKP isolates. Ten CRKP isolates were selected to determine the minimum bactericidal concentration. The checkerboard microdilution method was performed to determine the synergic effects of colistin combinations with either meropenem or amikacin on CRKP isolates. Time kill assays were used to evaluate the effectiveness of monotherapies and colistin- meropenem or colistin-amikacin combined therapies against 6 distinct sequence types of the CRKP isolates. The minimum inhibitory concentrations of colistin, meropenem and amikacin were 2 32, 4 256, and 1 16 μg/ml, respectively. The minimum bactericidal concentration of the antibiotics was either 1 time or 2 times of the minimum inhibitory concentration. Treatments of 6 CRKP isolates at 16 μg/ml meropenem or amikacin in addition to 2 μg/ml colistin completely killed 4 of them and suppressed the growth of 2 others (sequence type 76 and 11) while none of them showed bactericidal effects in the monotherapy. Our data suggest that colistin would be a valid therapeutic option against colistin-resistant CRKP isolates when it is used in combination with either meropenem or amikacin for treatment of CRKP infections in the Eastern Heilongjiang Province.